Astronomy and Climate-Earth System: Can Magma Motion under Sun-Moon Gravitation Contribute to Paleoclimatic Variations and Earth’s Heat? - Zhiren Joseph Wang; Xiaopei Lin (Advances in Astronomy)
Paleoclimate data have yielded variations with periods of ~23, ~40, and ~100 ky. Thermodynamic changes resulting from orbital eccentricity, obliquity, and precession have been ascribed as the cause of the variations although processes within the oceans and atmosphere may have too short memory to explain such variations. In this work, the dynamics of Sun-Moon gravitation (SMG) were explored for a rotating Earth and were determined to have a long memory in magma, a mostly ignored geophysical fluid with a mass ~3,400 times that of the atmosphere plus the oceans. Using the basic motion and gravitation (including obliquity) of the Sun and the Moon, we determined that SMG-induced magma motion could produce paleoclimatic variations with multiple periods (e.g., ~23, ~40, ~80, and ~100 ky), with considerable power for Earth’s heat. Such “reproducible” power could possibly maintain an energetic Earth against collapse, radioactivity, and cooling.